Determination of Ellenberg’s indicator values along an elevational gradient in Central Black Sea Region of Turkey - Kutbay, H.G.; Surmen, B. (Universiti Kebangsaan Malaysia, 2013)
The Central Black Sea Region has an unique vegetation because different vegetation types occurred. In the present study plant communities (from Mediterranean-type to temperate forests) in the Central Black Sea Region along an elevational gradient was evaluated on Ellenberg’s Indicator Values (EIVs). EIVs were calculated for nutrient availability, pH and temperature variables (nutrient availability (N), pH (R) and temperature (T)) with the help of weighted averages. Additionally, the vegetation of the study area was classified by using two way indicator species analyses (TWINSPAN) method and the interactions among plant species and EIVs were also studied by the help of Canonical Correspondence Analysis (CCA). We found some differences between our data and the previous data which were obtained from similar vegetation types with respect to EIV’s for nutrient availability, pH and temperature. Pteridium aquilinum, Fragaria vesca and Euphorbia amygdaloides var. amygdaloides may be used as an indicator of nutrient availability. There were significant differences among species regarding EIVs for temperature because the study area includes temperate and Mediterranean-type communities.